2022
DOI: 10.1155/2022/1240242
|View full text |Cite
|
Sign up to set email alerts
|

Xiao-Chai-Hu Decoction Ameliorates Poly (I:C)-Induced Viral Pneumonia through Inhibiting Inflammatory Response and Modulating Serum Metabolism

Abstract: Viral pneumonia is widespread, progresses rapidly, and has a high mortality rate. Developing safe and effective therapies to treat viral pneumonia can minimize risks to public health and alleviate pressures on the associated health systems. Xiao-Chai-Hu (XCH) decoction can be used in the treatment of viral pneumonia. However, the mechanisms of XCH on viral pneumonia remain unclear. In this study, poly (I:C) was used to establish a mouse model of viral pneumonia, and the therapeutic effects of XCH on viral pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Chen and colleagues discovered that taurine can attenuate sepsis-induced lung injury through anti-inflammatory actions and antioxidative stress, reducing overexpression of tumor necrosis factor (TNF)-α and IL-1β and neutrophil infiltration ( Chen, J. et al, 2021 ). Early studies also showed that abnormalities of the taurine metabolism of occurred in viral pneumonia and lipopolysaccharide-induced pulmonary injury ( Chen, F. et al, 2022 ). Hence, taurine is regarded as a potential agent for lung injury under various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Chen and colleagues discovered that taurine can attenuate sepsis-induced lung injury through anti-inflammatory actions and antioxidative stress, reducing overexpression of tumor necrosis factor (TNF)-α and IL-1β and neutrophil infiltration ( Chen, J. et al, 2021 ). Early studies also showed that abnormalities of the taurine metabolism of occurred in viral pneumonia and lipopolysaccharide-induced pulmonary injury ( Chen, F. et al, 2022 ). Hence, taurine is regarded as a potential agent for lung injury under various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[64] It has antiviral and anti-infective properties, it can be used for treating COVID-19. [65] However, XD could be a potential drug for the treatment of AP by acting on the key genes of mitogen-activated protein kinase 3 (MAPK3), IL-6, and tumor protein 53 (TP53). [64] Yi-Yi mixture Yi-Yi mixture, an efficient Chinese medicine preparation composed of 4 herbal medicines, has been used in clinical practice in China for the treatment of AP for over 20 years.…”
Section: Huoxueqingyi Decoctionmentioning
confidence: 99%
“…Anti-inflammatory and antioxidant Pancreatic and biliary duct retrograde infusions of 5.0% sodium taurocholate (SAP) [65] P2X7/NLRP3, ASC, caspase-1 IL-1β, Il-18…”
Section: Namementioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that, Qingwen Jiere mixture was able to treat viral pneumonia by regulating arginine, arachidonic acid, nicotinate, and nicotinamide metabolism processes (16). A recent study using untargeted metabolomics also indicated that the Xiaochaihu decoction could treat viral pneumonia by influencing serum metabolites involved in amino acids and taurine metabolism (17).…”
Section: Introductionmentioning
confidence: 99%